An Analysis of The English Gerund as Subject, Direct Object, Subject Complemet, and Object of Preposition - Raflis Raflis; Arozato Lase (Fakultas Sastra Universitas Ekasakti, 2018)
The problem in this journal is gerund, verbal ending -ing and serves as a noun. Gerund differs from grammar construction in English because it is able to convert a verb into a noun by adding -ing at the end of the verb. At the same time, there is also a continuous tense form that adds -ing at the end of the verb. For students who start learning English will be confused with the form -ing that can be a noun and also a verb in the same sentence. The method used is the method of distribution, the method of data analysis into object analysis is part of the language itself. Objects in the distribution method are always part or element of the language being observed. In analyzing the data, the authors use qualitative methods. Qualitative research is a type of social science research that collects and works with non-numerical data and which seeks to interpret the meaning of the data being analyzed. In this study, researchers used descriptive design with the aim to analyze gerund as subject, direct object, complement of subject, and object of preposition at Tempo magazine in 2015. The author finds gerund formulation as follows: Gerund as Subject (Main + Main Verb + Complement), gerund as Direct Object (Subject + Main Verb + Gerund), gerund as Subject Complement (Subject + to be + Gerund), and gerund as Object of Preposition (Subject + Primary Keyword + Preposition + Gerund). The study found that Tempo magazine used gerund in magazines with higher gerund percentages as the preposition object. There are 8 gerunds as the subject, 5 gerund as a direct object, 6 gerund as complementary subject, and 23 gerund as the preposition object.